Fentanyl-Induced cerebrocardial syndrome - L. Kh.-B. Akhmatkhanova; E. A. Kovaleva; I. S. Aliev; Kh. V. Korigova; E. V. Shevchenko; A. Yu. Simonova; G. R. Ramazanov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The clinical case is presented to demonstrate the importance of differential diagnosis of cerebral circulation disorders in patients with acute or chronic toxic effects of psychoactive substances. In the presented observation, a 50-year-old patient was taken to the N.V. Sklifosovsky Research Institute of SP with depression of the level of wakefulness to deep deafness, denies the fact of using psychoactive substances when collecting anamnesis, bilateral myosis, diffuse decrease in tone in all extremities. Computed angiotomography of the brain, transcranial dopplerography, magnetic resonance imaging of the brain, electroencephalography were performed – without obvious diagnostic findings. During a detailed examination in a neurological clinic, no data were obtained for a violation of cerebral circulation, a chemical and toxicological examination of urine and blood was performed, fentanyl was detected in biological media. Based on the literature data, however, damage to the nervous system usually occurs due to chronic intoxication and it is not always possible to detect psychoactive substances in biological environments. Due to respiratory depression, the patient was intubated and was on artificial ventilation for 72 hours until spontaneous respiration was restored. After repeated demand, the patient admitted the fact of using fentanyl allegedly to relieve pain, after which he refused further treatment. The conclusion is the need for a chemical and toxicological study of biological media in the case of a violation of consciousness of unclear genesis, however, damage to the nervous system usually occurs due to chronic intoxication and it is not always possible to detect psychoactive substances in biological media.